Effectiveness of bleaching agent on composite resin discoloration - Galih Sampoerno (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: The discoloration of teeth, especially anterior teeth, is one of aesthetic problems. The use of tooth bleaching agents for discolored natural teeth is becoming increasingly popular. Many dentists, however, get many problems when they conduct bleaching process since there is much composite filling on patient’s anterior teeth. Although many research have focused on the discoloration of composite resin after bleaching process, the problem still becomes debatable. Purpose: The purpose of this study was to investigate the difference of the discoloration between hybrid composite and nano composite before and after the application of tooth bleaching agent, 38% hydrogen peroxide. Methods: Eighteen disk-shaped specimens (5 mm) of each of two composite resins, hybrid and nano filler, were prepared. The each group was treated 3 times and the specimens were divided into two groups consisted of 9 specimens for each, and then immersed in black tea solutions for 72 hours. Next, after having staining and bleaching processes, the color of the specimens was measured with a optic spectrophotometer by using photo with type BPY-47 and digital microvolt. The differences of the light intensity among three measurements were then calculated. Afterwards, GLM MANOVA Repeated Measure and parametric analysis (Independent t-test and Paired t-test) were then used to analyze the data. Results: After staining process, it is then known that the nano composite had more discoloration and more affected by the black tea solution than the hybrid one. Conclusion: After bleaching, the discoloration was finally removed completely from both hybride and nano filler composite resins and became brighter from the baseline color.Latar belakang: Salah satu problem estetik adalah adanya perubahan warna pada gigi anterior. Peningkatan pemakaian bahan bleaching semakin popular. Banyak dokter gigi mempunyai problem ketika mereka akan melakukan proses bleaching dan ditemukan banyak tumpatan komposit pada gigi anteriornya. Meskipun telah banyak penelitiahan yang dilakukan tetapi masalah ini masih menjadi pro dan kontra. Tujuan: Melihat perbedaan perubahan warna antara komposit hybrid dan komposit nano sebelum dan sesudah terpapar bahan pemutih gigi hidrogen peroksida 38%. Metode: Tiap kelompok mendapatkan perlakuan 3 kali. Dipersiapka 18 spesimen berbentuk tabung (5 mm) dan dibagi menjadi 2 kelompok masing-masing 9 untuk resin komposite hybrid dan komposit nano. Direndam larutan teh hitam selama 72 jam. Perubahan warna diukur dengan spektrofotometer tipe BPY-47 dan mikrovolt digital, baik sebelum, setelah perendaman larutan teh hitam dan setelah proses bleaching. Perbedaan intensitas cahaya dihitung dengan GLM MANOVA Repeated Measuse dan analisa parametrik. Hasil: Setelah perendaman teh hitam, komposit nano mempunyai perubahan warna yang lebih gelap dibandingkan komposit hybrid. Setelah bleaching, baik komposite hybrid dan komposit nano kembali ke warna aslinya. Tetapi perubahan warna komposit nano lebih besar dari pada komposit hybrid. Kesimpulan: Setelah bleaching, baik resin komposit hybrid dan nano menjadi lebih terang dari warna aslinya.